Theoretical and experimental research of hydrogen storage properties of Mg and Mg-Al hydrides; Journal of Alloys and Compounds; Vol. 938 - Lyu Jinzhe; Elman R. R. Roman Romanovich; Svyatkin L. A. Leonid Aleksandrovich; Kudiyarov V. N. Victor Nikolaevich (2022, 2022)
Title screen